2008
DOI: 10.1136/hrt.2007.132092
|View full text |Cite
|
Sign up to set email alerts
|

The bicuspid aortic valve: an integrated phenotypic classification of leaflet morphology and aortic root shape

Abstract: A comprehensive BAV phenotype includes aortic shape. Type 1 BAV is associated with male gender and normal aortic shape but a larger sinus diameter. Type 2 leaflet morphology is associated with ascending aorta dilatation , larger arch dimensions and higher prevalence of myxomatous mitral valve disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
313
7
19

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 393 publications
(364 citation statements)
references
References 29 publications
25
313
7
19
Order By: Relevance
“…Interestingly, Fazel et al (2008) found the highest prevalence of right coronary and noncoronary cusp fusion and the highest mean grade of aortic valve insufficiency in the cluster of BAV patients with dilatation of the tubular ascending aorta and aortic arch. These findings correlate appropriately with the data from the rheological and echocardiographic studies by Schaefer et al, (2008). Moreover, the retrospective study by Fazel et al, (2008) included only a selected (i.e., non-consecutive) cohort of BAV patients, for whom thoracic aortic imaging data were available for analysis.…”
Section: Clustering Of Patients With Bav Aortopathysupporting
confidence: 62%
See 2 more Smart Citations
“…Interestingly, Fazel et al (2008) found the highest prevalence of right coronary and noncoronary cusp fusion and the highest mean grade of aortic valve insufficiency in the cluster of BAV patients with dilatation of the tubular ascending aorta and aortic arch. These findings correlate appropriately with the data from the rheological and echocardiographic studies by Schaefer et al, (2008). Moreover, the retrospective study by Fazel et al, (2008) included only a selected (i.e., non-consecutive) cohort of BAV patients, for whom thoracic aortic imaging data were available for analysis.…”
Section: Clustering Of Patients With Bav Aortopathysupporting
confidence: 62%
“…This phenotypic classification has been proposed as a clinical and a research tool in order to precisely define BAV subgroups based on the combination of cusp morphology and proximal aortic shape. Another retrospective echocardiographic study demonstrated, analogously with Schaefer et al (2007Schaefer et al ( , 2008, that fusion of the right coronary and non-coronary cusps correlated with the more rapid growth of ascending aortic diameter in the pediatric population (Holmes et al, 2007). The pathogenetic background for clinical observation of the specific aortic shapes in BAV patients with different morphologic cusp fusion patterns has been elucidated in detailed in vivo rheological studies using sophisticated 4D magnetic resonance imaging .…”
Section: Different Cusps Fusion Patterns In Bav Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…15) In an echocardiographic study of BAV by Schaefer and associates, the overall prevalence of myxomatous MV was 4.7% and varied according to the morphology of the aortic cups: its prevalence was 2.6% in the fused right and left cusp type and 13% in the fused right and non-coronary cusp type. 16) Roberts et al reported the combination of mitral valve prolapse and BAV, which is rare; however, a more detail examination to detect mitral valve dysfunction is recommended for surgical BAV patients. 17) Sievers and associates attempted to establish a classification system based on 5 years of data collected from the surgical specimens of 304 patients.…”
Section: Pathophysiology Morphology and Aortopathy Of Bicuspid Aortimentioning
confidence: 99%
“…(24)(25)(26)(27)(28) Despite this challenge, the many prognostic this information is implicit in most current classifications. (27) In addition to valve morphology, more complete phenotypic classifications also include typing of aortic dilation.…”
Section: Phenotypementioning
confidence: 99%